A different view on the pathophysiology of Parkinson’s disease: A descendent neurochemical hypothesis? - Yuluğ, Burak; Ozansoy, Mehmet; Çankaya, Şeyda (Wolters Kluwer, 2019)
It has been already shown that Parkinson’s disease (PD) is characterized by a prominent degeneration in substantia nigra (SN)neurons. Growing evidence suggests that there is a latent period of PD associated with slight non-motor findings such as olfactorydys function (Dickson et al., 2018). However, the potential biomarker role of olfactory dysfunction in PD has been a topic of great interest in the last years (Raskin et al., 1990; Dicksonet al., 2018). The classical hypothesis of Braak suggests that PD begins as a synucleinopathy in the lower brainstem or in the olfactorybulb (OB) that progresses rostrally to the SN and amygdalato cause parkinsonism at a later stage of the disease (Burkeet al., 2008). However, Braak’s hypothesis should be cautiously interpreted since this scheme is not based on the distribution of neuronal cell loss, but on the distribution of the accumulation of abnormal ?-synuclein aggregates which leaves unanswered how it relates to the progression of neurochemical changes.
Keywords: Parkinson; Pathophysiology; Neurochemical